Rekonstruksi Politik Hukum Undang-Undang Aparatur Sipil Negara Berbasis Nilai Keadilan - Rahmat Saputra (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2021)
The purpose of the study was to find and analyze the protection of the law of honorary staff and PPPK after the highest number 5 of 2014 concerning state civilian apparatus and to find and analyze the form of new construction of legal politics of state civilian apparatus based on the value of justice. The method used in this study is the method of normative legal research with legislation approaches and case approaches. The results of the study of the differences in PNS and PPPK which are not based on the nature and type of work have violated the issue of the issue that mandates the management of ASN employees who are nationally integrated. The ASN Law violates the principle of legal certainty, especially in relation to the clarity of employment between the government and PPPK employees. The absence of certainty and protection to become a permanent employee of the state, including honorary staff, non-permanent employees, non-civil servant employees, and contract staff. In an effort to provide legal justice and certainty for PPPK and honorary staff, non-permanent employees, permanent non-civil servants, and contract workers who have been serving the government, it is expected to be the preparation and discussion of the bill on changes in the ASN Law.